Deficiency-related pancytopenia: retrospective study of 34 cases (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Introduction: The goal of this work was to determine the place of the deficiency-related etiology inPancytopenia, facilitation of the diagnosis and the definition of the epidemiological, clinical and paraclinicalcharacteristics of deficiency-related Pancytopenia.Methodology: It is a retrospective study of 112 Pancytopenia cases of which 34 were Deficiency-relatedPancytopenia taken from a data taken from a period of 5 years (2006-2010) from the HematologyLaboratory of the Mohammed V Teaching Military Hospital Rabat.Results: 112 Pancytopenia cases were found. The result from a comparison between 2 groups of patientsof medium age with or without etiological deficiency-related Pancytopenia by the “Student Test” was t =0.001070744